The Future of Postgraduate Medical Education in Canada. (September 2015) - Busing, Nick; Harris, Ken; MacLellan, Anne-Marie; Moineau, Geneviève; Oandasan, Ivy; Rourke, James; Saxena, Anurag
<x xml:space="preserve">Abstract</x> The Future of Medical Education in Canada Postgraduate (FMEC PG) Project was launched in 2010 by a consortium of four organizations: the Association of Faculties of Medicine of Canada, the Collège des Médecins du Québec, the College of Family Physicians of Canada, and the Royal College of Physicians and Surgeons of Canada. The FMEC PG study set out to review the state of the Canadian postgraduate medical education (PGME) system and make recommendations for improvements and changes. The extensive process included literature reviews, commissioned papers, stakeholder interviews, international consultations, and dialogue with the public and learners. The resulting key findings and 10 recommendations, published in a report in 2012, represent the collective vision of the consortium partner organizations for PGME in Canada. Implementation of the recommendations began in 2013 and will continue beyond 2016. In this article, the authors describe the complex process of developing the recommendations, highlight several recommendations, consider implementation processes and issues, and share lessons learned to date. They reflect on the ways in which the transformation of a very complex and complicated PGME system has required many stakeholders to work together on multiple interventions simultaneously. Notwithstanding the challenges for the participating organizations, changes have been introduced and sustainability is being forged. Throughout this process, the consortium partners and other stakeholders have continued to address the social accountability role of all physicians with respect to the public they serve.